2014
DOI: 10.1186/1471-2164-15-480
|View full text |Cite
|
Sign up to set email alerts
|

Detection of copy number variations and their effects in Chinese bulls

Abstract: BackgroundCopy number variations (CNVs) are a main source of genomic structural variations underlying animal evolution and production traits. Here, with one pure-blooded Angus bull as reference, we describe a genome-wide analysis of CNVs based on comparative genomic hybridization arrays in 29 Chinese domesticated bulls and examined their effects on gene expression and cattle growth traits.ResultsWe identified 486 copy number variable regions (CNVRs), covering 2.45% of the bovine genome, in 24 taurine (Bos taur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 64 publications
1
64
2
1
Order By: Relevance
“…However, there have been no reports about the function of the CYP4A11 gene in cattle. We previously confirmed that the cattle CYP4A11 gene was located within CNVR44 that encompasses QTLs that alter economic traits like meat quality and milk production21. This location suggests that the copy number of CYP4A11 must be variable, which we hypothesized may have genetic effects that can be conveyed to phenotypes.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…However, there have been no reports about the function of the CYP4A11 gene in cattle. We previously confirmed that the cattle CYP4A11 gene was located within CNVR44 that encompasses QTLs that alter economic traits like meat quality and milk production21. This location suggests that the copy number of CYP4A11 must be variable, which we hypothesized may have genetic effects that can be conveyed to phenotypes.…”
supporting
confidence: 57%
“…This reflected the positive effect of multiple copies of CYP4A11 on growth, which may be attributed to the location of CYP4A11 in the CNVR44 which includes QTLs that are linked to economic traits21. As previous reports showed, some genes were located within CNVRs that directly overlapped with QTLs for body weight, marbling score, and somatic cell count38, or were partly encompassed by QTLs for body weight, carcass weight, and breast muscle weight3940.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Although there are numerous breeds of cattle and sheep both within and outside China, and no less than 10 studies report on the genomes of cattle, just two papers investigate CNVs in the sheep genome [9][10][11][12][13]. expressed as a decimal, whose GenCall score is greater than the specified threshold) less than 98% were excluded.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Modal analysis [4,5] is a kind of modern method of studying the dynamic characteristics of the structure. It is mainly used to determine the vibration characteristics of the structure and the parts of the machine, including natural frequency and vibration.…”
Section: The Finite Element Modal Analysis Theorymentioning
confidence: 99%